2014
DOI: 10.1177/0310057x1404200105
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial of Parecoxib, Celecoxib and Paracetamol as Adjuncts to Patient-Controlled Epidural Analgesia after Caesarean Delivery

Abstract: The benefit of combining non-opioid analgesics with neuraxial opioids for analgesia after caesarean delivery has not been clearly established. larger doses of paracetamol or cyclooxygenase-2 inhibitors have not been evaluated. A randomised, double blind, double-dummy, parallel group placebo-controlled clinical trial was conducted among women having elective caesarean delivery under spinal anaesthesia, followed by pethidine patient-controlled epidural analgesia. Patients received placebos (group C); intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…In 2009, a Cochrane review reported that a single dose of 20 or 40 mg parecoxib, by either intramuscular or i.v. route, is an effective medication for acute postoperative pain and it can reduce total requirement of supplemental analgesia over a 24‐h period . However, none of the studies within this meta‐analysis evaluated the effects of parecoxib in CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, a Cochrane review reported that a single dose of 20 or 40 mg parecoxib, by either intramuscular or i.v. route, is an effective medication for acute postoperative pain and it can reduce total requirement of supplemental analgesia over a 24‐h period . However, none of the studies within this meta‐analysis evaluated the effects of parecoxib in CD.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for this double‐blind, randomized, parallel‐group, placebo‐controlled trial was approved by the Siriraj Institutional Review Board (EC090/2557). Relatively few studies have been conducted on the efficacy of parecoxib after CD and no studies have compared the efficacy of parecoxib with placebo. The sample size was calculated based on data from Ng et al ., who reported a 22‐mg difference in postoperative morphine consumption compared with placebo after total abdominal hysterectomy – a common gynecological procedure .…”
Section: Methodsmentioning
confidence: 99%
“…There are three studies using COX-2 inhibitors for post-CS analgesia. [575859] One study evaluated single dose of oral celecoxib 200 mg added to PCEA and compared it to analgesia provided by PCEA only. [57] There was no difference in the total drug consumption in either group.…”
Section: Non-steroidal Anti-inflammatory Drugs and Acetaminophen/paramentioning
confidence: 99%
“…compared the combination of oral celecoxib and intravenous parecoxib to paracetamol for post-CS analgesia. [59] They found that the combination of COX-2 inhibitors to be more effective in reducing analgesic requirement. Celecoxib and parecoxib provide a safe profile for both surgical patients and breastfeeding mothers.…”
Section: Non-steroidal Anti-inflammatory Drugs and Acetaminophen/paramentioning
confidence: 99%
“…The goal of postpartum pain management is to reduce total opioid consumption and its side effects, and to facilitate early ambulation and interaction with the newborn [79]. The efficacy of neuraxial opioids for post cesarean delivery pain is well documented in the literature [80][81][82], and its use with multimodal analgesia consisting of non-opioid medications, including paracetamol, NSAIDs, and COX-2 inhibitors, has been shown to further reduce the amount of morphine consumed postoperatively [79,[83][84][85][86][87]. No clear difference, however, has been demonstrated between these adjuncts [85].…”
Section: Postpartum Pain Managementmentioning
confidence: 99%